THE PREDICTION OF FINANCIAL DISTRESS IN PROPERTY COMPANIES IN SOUTHEAST ASIAN: INDONESIA, SINGAPORE, AND MALAYSIA - Ghoni, Muhammad Abdul; Maksum, Asep; Jaelani, Abdul Qadir; Yunus, Noor’ain Mohamad (Fakultas Ekonomi dan Bisnis, Universitas Airlangga, 2025)
Introduction: This study aims to assess and evaluate the financial distress state of a sample including 204 data points from 35 enterprises in Southeast Asia, specifically Indonesia, Malaysia, and Singapore. Methods: This study analyzes the effects of Covid-19 on these enterprises, specifically concentrating on the likelihood of financial hardship as assessed by Edward Altman's Z-score model. Results: Evidence indicates that property businesses listed on the Indonesia, Malaysia, and Singapore Stock Exchanges had greater financial difficulties during the Covid-19 period compared to the post-Covid period, aligning with observations at the ASEA Landmark level. The projected likelihood of default for publicly traded enterprises rose significantly during the Covid pandemic. Conclusion and suggestion: The data reveal that the Z-score's efficacy in predicting bankruptcy markedly declined during the financial crisis. The data indicate that Covid-19 is causing financial pain to enterprises in Southeast Asia.